Comparison of radiofrequency and monopolar electrocautery tonsillectomy - AKSOY, FADLULLAH; AKSOY, FEYZA MÜBERRA; ÖZTURAN, ORHAN; Ozturan, ORHAN; VEYSELLER, B.; YILDIRIM, Y. S.; DEMIRHAN, H. (My University, 2010)
Objectives: To compare the efficacy and safety of radiofrequency and monopolar electrocautery tonsillectomy, regarding operation duration and tonsillectomy morbidity, including post-operative pain and haemorrhage and tonsillar fossa healing, in patients with recurrent chronic tonsillitis.